Critical review of Islamic work ethic literature across diverse organization and its future direction - Atiya, Nikmatul; Widiastuti, Tika; Rusanti, Ega (Nur Science Institute, 2024)
This research systematically evaluates the literature on Islamic Work Ethics (IWE) and divides it into several topics, i.e., leadership, organization, employee behavior, and employee performance. Furthermore, this research highlights the application of Islamic Work Ethics in various organizations. Using a qualitative design, this research applies a Systematic Literature Review to analyze 62 Scopus-indexed articles. The articles analyzed are articles with quantitative research that provide empirical evidence of the influence and cause-and-effect relationships of implementing Islamic Work Ethics in various organizations. Islamic Work Ethics has been implemented in almost all organizational sectors, both government and non-government, as well as public and private organizations. The outcomes of implementing Islamic Work Ethics depend on the type of organization and its members' level of Islamic Work Ethics. The findings show that the subtopics of organizational commitment and organizational citizenship behavior and their causal relationships with IWE are more closely related than other topics. This research only involves articles with quantitative methods for analysis. However, it is very important to see the impact of implementing Islamic Work Ethics in various organizations.